Development of a novel bivalent vaccine candidate against hepatitis A virus and rotavirus using reverse vaccinology and immunoinformatics - Hassan Yarmohammadi; Abbas Akhavan Sepahi; Mojtaba Hamidi-fard; Mohammadreza Aghasadeghi; Golnaz Bahramali (Journal of Virus Eradication)
The hepatitis A virus (HAV) and rotavirus are mainly transmitted through fecal-oral and person-to-person contact, and cause severe gastrointestinal complications and liver disease. This work used reverse vaccinology and immunoinformatic methods to create a novel bivalent vaccine against rotavirus and HAV. The amino acid sequences of HAV-rotavirus proteins (VP1 and VP8∗) were retrieved from the GenBank database. Various computational approaches were employed to predict highly conserved regions and the most immunogenic B-cell and T-cell epitopes of VP8 and VP1 of rotavirus and HAV proteins in both humans and BALB/c. Moreover, the predicted fusion protein was analyzed regarding primary and secondary structures and homology validation. In this study, we used two highly conserved peptide sequences of VP8 and VP1 of rotavirus and HAV that induce T and B cell immunogenicity. According to T-cell epitope prediction, this area comprises 2713 antigenic peptides for HLA class II and 30 HLA class I antigenic peptides, both of which are virtually entirely conserved in the Iranian population. In this study, validation as well as analysis of the secondary and three-dimensional structure of the VP8∗-rotavirus + AAY + HAV-VP1 fusion protein, with the aim of designing a multi-epitope vaccine with different receptors. TLR 3, 4 high immunogenic binding ability with immunological properties and interaction between multi-epitope target and TLR were predicted, and it is expected that the target fusion protein has stable antigenic potency and compatible half-life. The above is suggested as a universal vaccination program.